From policy to resources: programming, computational thinking and mathematics in the Danish curriculum - Elicer, Raimundo; Lindenskov Tamborg, Andreas (NOMAD Nordic Studies in Mathematics Education, 2023)
This article investigates the relations between mathematics and programming and computational thinking (PCT). In scholarly knowledge, PCT is juxtaposed as an aid to mathematical problem solving, but also integrated as a collection of practices common to both domains. This knowledge is being turned into curriculum and teaching resources developed for Danish compulsory schools (students aged 6–15), in the context of a pilot project to embed a new technology comprehension subject into mathematics. In the curriculum, PCT is being juxtaposed to mathematics. The teaching resources are predominantly integrated, but lacking connections to mathematical problem solving and modelling. These misalignments are both missed opportunities and a leeway for a cautious integration in teaching practice.